The effects of cycle and treadmill desks on work performance and cognitive function in sedentary workers: A review and meta-analysis. - Podrekar, Nastja; Kozinc, Žiga; Šarabon, Nejc (Work, 2020)
BACKGROUND: Sedentary behavior has been recognized as an important risk factor in the development of several chronic diseases. Active workstations have been proposed as an effective countermeasure. While such interventions likely reduce sedentary time, concerns regarding the effects on work performance and cognitive function remain. OBJECTIVE: To use meta-analyis to critically evaluate the work performance and cognitive function effects of cycle and treadmill desks as workplace interventions against sedentary behavior. METHODS: In February 2018, a data search was conducted. Parallel and crossover design studies evaluating workplace interventions compared to conventional seated conditions were included. RESULTS: Eighteen studies met the inclusion criteria. Both interventions reduced typing speed (cycling: SMD = –0.35, p = 0.04; treadmill: SMD = –0.8, p < 0.001). The number of typing errors significantly increased during cycling interventions (SMD = 0.39, p = 0.004). No effect was found for the selective attention tests. However, there was an improvement in recall ability (SMD = 0.68, p = 0.003). CONCLUSION: Cycle and treadmill desks affect work performance, but most likely not due to a decrease in cognitive function. Further research is needed to determine whether the degree of work performance decline is acceptable, considering the many positive effects of implementing active workstations in the office environment.